Efektivitas Kerja Perangkat Desa dalam Penyelesaian Administrasi di Desa Bawosaloo Dao-Dao Kecamatan Hilimegai - Waruwu, Darman Syukur Putra; Waruwu, Meiman Hidayat; Telaumbanua, Eliagus; Bate’e, Maria Magdalena (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the effectiveness of village apparatus work in completing administration in Bawosalo’o Dao-Dao Village, Hilimegai District, South Nias Regency. Villages as the leading government unit have an important role in providing effective public services to the community. However, the effectiveness of village apparatus work is often not optimal due to limited human resources, lack of training, weak work discipline, and lack of application of information technology. The focus of this study includes the level of effectiveness of village apparatus work and factors that influence the completion of village administration. The research method used is a qualitative approach with data collection through interviews, observations, and documentation. This study found that the effectiveness of village apparatus work is influenced by individual competence, organizational culture, leadership, and the work systems and procedures applied. The low level of attendance and work discipline of village apparatus are the main challenges that affect the completion of administration. This study is expected to provide strategic recommendations to improve the effectiveness of village apparatus work through training, competency development, application of information technology, and improvement of organizational culture and leadership.